(Military) Masculinity and a Feminized Europe: The Gender Politics of the Lasky Diary - Gerund, Katharina (The Diary of Lt. Melvin J. Lasky: Into Germany at the End of World War II, 2022)
This essay examines the gender politics of Melvin Lasky’s war diary. It analyzes Lasky’s masculine self-fashioning as a historian and intellectual and as a young soldier. It showcases how he negotiates his gendered identity vis-à-vis the hegemonic masculinity of his time. Furthermore, it examines how the document casts the transatlantic relationship in highly gendered terms: Europe appears as a feminized (and sexualized) landscape that is liberated/conquered by a predominantly male U.S. military. <